Enhancing Bank Performance: Integrating Enterprise Risk Management with Mobile Banking Applications - Harsono Yoewono; Ananto Prabowo (Universitas Hayam Wuruk Perbanas, 2024)
This study investigates how the implementation of mobile banking and enterprise risk management (ERM) contributes to the success of financial institutions in a rapidly evolving financial environment. To understand the relationship between ERM, mobile banking adoption, and bank performance, we surveyed 250 senior bankers from the 25 largest banks in Indonesia using Partial Least Squares Structural Equation Modeling (PLS-SEM). Our findings indicate that effective ERM implementation positively affects bank performance. Mobile banking enhances customer convenience, streamlines operations, and broadens market reach, increasing customer satisfaction, operational efficiency, and profitability. Additionally, using mobile banking applications mediates the positive indirect impact of ERM on bank performance. This research highlights that ERM's effect on Indonesian banking performance is partly mediated by adopting mobile banking applications. The study contributes to the literature on RBV theory, which suggests that banks can create innovative ERM strategies and leverage its unique resources, such as mobile banking, to remain competitive and sustain their performance. The innovation aligns with the principles of TAM, which highlights the significance of perceived usefulness and ease of use in technology adoption.